CD13 Inhibition Enhances Cytotoxic Effect of Chemotherapy Agents - Zhang, Jian; Fang, Chunyan; Qu, Meihua; Wu, Huina; Wang, Xuejuan; Zhang, Hongan; Ma, Hui; Zhang, Zhaolin; Huang, Yongxue; Shi, Lihong; Liang, Shujuan; Gao, Zhiqin; et al. (Frontiers in Pharmacology, 2018)
Multidrug resistance (MDR) of hepatocellular carcinoma is a serious problem. Although CD13 is a biomarker in human liver cancer stem cells, the relationship between CD13 and MDR remains uncertain. This study uses liver cancer cell model to understand the role of CD13 in enhancing the cytotoxic effect of chemotherapy agents. Cytotoxic agents can induce CD13 expression. CD13 inhibitor, bestatin, enhances the antitumor effect of cytotoxic agents. Meanwhile, CD13-targeting siRNA and neutralizing antibody can enhance the cytotoxic effect of 5-ﬂuorouracil (5FU). CD13 overexpression increases cell survival upon cytotoxic agents treatment, while the knockdown of CD13 causes hypersensitivity of cells to cytotoxic agents treatment. Mechanistically, the inhibition of CD13 leads to the increase of cellular reactive oxygen species (ROS). BC-02 is a novel mutual prodrug (hybrid drug) of bestatin and 5FU. Notably, BC-02 can inhibit cellular activity in both parental and drug-resistant cells, accompanied with significantly increased ROS level. Moreover, the survival time of Kunming mice bearing H22 cells under BC-02 treatment is comparable to the capecitabine treatment at maximum dosage. These data implicate a therapeutic method to reverse MDR by targeting CD13, and indicate that BC-02 is a potent antitumor compound.